IMPLEMENTASI ALAT PENGUSIR BURUNG MENGGUNAKAN METODE SUARA OTOMATIS DAN SOLAR CELL (STUDI KASUS: PERSAWAHAN DARURRUHAMA KOTA PALEMBANG) - Prayitno, Rudi (JURNAL TELISKA, 2025)
Efforts to control pests in rice agricultural land continue to be implemented to improve crop yields through chemical and mechanical methods. One of the main pests that disrupt farmers is birds, such as sparrows and finches, which consume rice seeds and cause significant losses, especially when the rice begins to fill. Rice production in South Sumatra reaches 55,532 tons per year, with potential yield losses due to bird attacks reaching 30%. Various repellent methods, such as setting traps and using protective nets, have been applied, but farmers still rely on traditional methods that are less effective. This research aims to design a solar cell-based bird repellent device, named Audio Sweep, using physical methods to utilize sound waves at specific frequencies. This method is expected to be more environmentally friendly and effective. The research was conducted using a Research and Development (R&D) approach up to the prototyping and initial testing stages in the Darurruhama rice field area in Palembang. The results of the trials show that this device is capable of generating sound waves at frequencies effective in repelling birds, while also being equipped with a monitoring system based on the ESP 32-CAM microcontroller. This research not only produces an innovative product but also provides practical solutions to reduce yield losses due to bird pest attacks, supports sustainable agriculture, and contributes to the vision of Indonesia Emas 2024.